Michał Koza, syn Andrzeja z Domasławia, pleban w Słupcy w latach 1439-1447. Wypisy z akt oficjalatu gnieźnieńskiego - Czyżak, Marta (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
The article presents the person of Michał son of Andrzej of Domasław, parson at Słupca (1439-1447), a town of the bishops of Poznań, former notary of the Gniezno consistory. Emphasis is placed on his involvement for the parish, especially his activity connected with his experience as notary (cases held at the Gniezno consistory in defense of the parish benefice and legates for the Słupca parish, concern for documentation of the legates). The study contains also a list of parsons in Słupca in the first half of the 15th century. The whole is complemented by excerpts from consistory acts showing the personal decisions of Michał of Domasław (resignation from the practice of the profession of notary, testament) as well as his activity as parson in Słupca.